Epigastric Hernias in Children: A Personal Series and Systematic Review of the Literature - Tinawi, Georges K.; Stringer, Mark D. (European Journal of Pediatric Surgery, 2020)
Epigastric hernias are relatively uncommon in children, and there is a paucity of literature on their incidence, presenting features, natural history, and surgical outcomes. A systematic review was conducted according to PRISMA guidelines. Articles describing the incidence, outcome, and interventions for pediatric epigastric hernias, both open and laparoscopic, were analyzed. Eight relevant articles published between 1975 and 2019 were included in the analysis. Of 81 children, 58% were females, 35% were symptomatic and 8% were multiple. All hernias contained preperitoneal fat only and were repaired using standard open surgery or laparoscopic techniques. No recurrences were recorded. In a personal series of 37 hernias in 36 children of median age 4 years, there were no recurrences; however, this series included two children with a recurrent or persistent epigastric hernia after surgery by others. Epigastric hernias in children are relatively uncommon. They typically contain only preperitoneal fat but more than a third are symptomatic. Standard open repair can be undertaken with minimal morbidity. Laparoscopic repair takes longer and provides a marginal cosmetic benefit.
Keywords: abdominal wall hernia; ventral hernia; minimally invasive surgery